Tumor-derived exosomes modulate PD-L1 expression in monocytes - Haderk, Franziska; Warnken, Uwe; Benner, Axel; Zenz, Thorsten; Diederichs, Sven; Zapatka, Marc; Lichter, Peter; Seiffert, Martina (Science immunology, 2017)
Messaging with RNAs Understanding interactions between tumor cells and immune cells is essential for tailoring immunocentric therapies to tumors. Here, Haderk et al. have identified a key role for tumor-derived exosomes in modulating immune responses to chronic lymphocytic leukemia (CLL). They report that CLL-derived exosomal RNAs promote monocytes in CLL patients to adopt an immunosuppressive phenotype, including promoting expression of PD-L1. They identify noncoding RNA hY4 as a key functional component of CLL-derived exosomes and show that hY4 promotes exosome-dependent skewing of monocytes in a TLR7-dependent manner. Using mouse models, they found that inhibition of TLR7 delayed progression of CLL, opening up the possibility that the TLR7 pathway could be therapeutically targeted in CLL. In chronic lymphocytic leukemia (CLL), monocytes and macrophages are skewed toward protumorigenic phenotypes, including the release of tumor-supportive cytokines and the expression of immunosuppressive molecules such as programmed cell death 1 ligand 1 (PD-L1). To understand the mechanism driving protumorigenic skewing in CLL, we evaluated the role of tumor cell-derived exosomes in the cross-talk with monocytes. We carried out RNA sequencing and proteome analyses of CLL-derived exosomes and identified noncoding Y RNA hY4 as a highly abundant RNA species that is enriched in exosomes from plasma of CLL patients compared with healthy donor samples. Transfer of CLL-derived exosomes or hY4 alone to monocytes resulted in key CLL-associated phenotypes, including the release of cytokines, such as C-C motif chemokine ligand 2 (CCL2), CCL4, and interleukin-6, and the expression of PD-L1. These responses were abolished in Toll-like receptor 7 (TLR7)-deficient monocytes, suggesting exosomal hY4 as a driver of TLR7 signaling. Pharmacologic inhibition of endosomal TLR signaling resulted in a substantially reduced activation of monocytes in vitro and attenuated CLL development in vivo. Our results indicate that exosome-mediated transfer of noncoding RNAs to monocytes contributes to cancer-related inflammation and concurrent immune escape via PD-L1 expression. Transfer of exosomal RNA from leukemic cells to monocytes induces immunosuppression. Transfer of exosomal RNA from leukemic cells to monocytes induces immunosuppression.
Gesehen am 06.11.2018